Pemberdayaan Masyarakat Pesisir Melalui Pengembangan Dan Pengolahan Berbasis Sumber Daya Alam Di Kecamatan Tanete Rilau Kabupaten Barru - Ernawati S. Kaseng; Nahriana Nahriana; Pince Salempa; Firdaus W. Suhaeb (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The aim of community service activities through the Community Partnership Program, is to provide knowledge and skills for diversification of processed sea fish, such as sea fish pepes, to PKM partners. It is hoped that through this PKM activity, it can motivate housewives of fishermen and teenage girls to drop out of school as well as administrators and group members to develop processed fish products. The method of implementing the Community Partnership Program (PKM), namely through training, demonstrations, and mentoring that is equipped with learning by doing techniques. To increase the knowledge and skills of women fishing partner groups, the approach used is the Participatory Rural Appraisal (PRA) approach. The results of the PKM activities show that increased knowledge and skills of housewives and farmers who drop out of school about the benefits and nutritional value contained in sea fish, and how to choose sea fish that can be pepes, and the process or method of making sea fish pepes. The emergence of a creative and innovative spirit during the accompaniment of the economic value of soft spiny pepesmanis fish can be used as a new business alternative so that later it can increase their family income